Sub-40 fs pulses at 1.8 mu m and MHz repetition rates by chirp-assisted Raman scattering in hydrogen-filled hollow-core fiber - Loranger, Sebastien; Russell, Philip St. John; Novoa, David (Journal of the Optical Society of America B-Optical Physics, 2020)
The possibility to perform time-resolved spectroscopic studies in the molecular fingerprinting region or extending the cutoff wavelength of high-harmonic generation has recently boosted the development of efficient mid-infrared (mid-IR) ultrafast lasers. In particular, fiber lasers based on active media such as thulium or holmium are a very active area of research since they are robust, compact, and can operate at high repetition rates. These systems, however, are still complex, are unable to deliver pulses shorter than 100 fs, and are not yet as mature as their nearinfrared counterparts. Here, we report the generation of sub-40 fs pulses at 1.8 gm, with quantum efficiencies of 50% and without the need for post-compression, in hydrogen-filled, hollow-core photonic crystal fiber pumped by a commercial high-repetition-rate 300 fs fiber laser at 1030 nm. This is achieved by pressure-tuning the dispersion and avoiding Raman gain suppression by adjusting the chirp of the pump pulses and the proportion of higher-order modes launched into the fiber. The system is optimized using a physical model that incorporates the main linear and nonlinear contributions to the optical response. The approach is average power-scalable, permits adjustment of the pulse shape, and can potentially allow access to much longer wavelengths. (C) 2020 Optical Society of America
CRIS-Team WoS Importer:2021-01-08